LINE-1 and Alu methylation signatures in autism spectrum disorder and their associations with the expression of autism-related genes - Thanit Saeliw; Tiravut Permpoon; Nutta Iadsee; Tewin Tencomnao; Valerie W. Hu; Tewarit Sarachana; Daniel Green; Chanachai Sae-Lee (Scientific Reports, 2022)
Abstract Long interspersed nucleotide element-1 (LINE-1) and Alu elements are retrotransposons whose abilities cause abnormal gene expression and genomic instability. Several studies have focused on DNA methylation profiling of gene regions, but the locus-specific methylation of LINE-1 and Alu elements has not been identified in autism spectrum disorder (ASD). Here we interrogated locus- and family-specific methylation profiles of LINE-1 and Alu elements in ASD whole blood using publicly-available Illumina Infinium 450 K methylation datasets from heterogeneous ASD and ASD variants (Chromodomain Helicase DNA-binding 8 (CHD8) and 16p11.2del). Total DNA methylation of repetitive elements were notably hypomethylated exclusively in ASD with CHD8 variants. Methylation alteration in a family-specific manner including L1P, L1H, HAL, AluJ, and AluS families were observed in the heterogeneous ASD and ASD with CHD8 variants. Moreover, LINE-1 and Alu methylation within target genes is inversely related to the expression level in each ASD variant. The DNA methylation signatures of the LINE-1 and Alu elements in ASD whole blood, as well as their associations with the expression of ASD-related genes, have been identified. If confirmed in future larger studies, these findings may contribute to the identification of epigenomic biomarkers of ASD.